JUST LIKE BLACK, ONLY BETTER: POOR WHITE IN ANTEBELLUM SOUTH OF AMERICA DEPICTED IN SOLOMON NORTHUP'S NOVEL TWELVE YEARS AS A SLAVE - Rasiah, Rasiah; Putra, Ansor; Masri, Fina Amalia; Arman, Arman; Pardilla, Suci Rahmi (Diksi, 2021)
(Title: Just Like Black, Only Better: Poor White in Antebellum South of America Depicted in Solomon Northup's Novel "Twelve Years as A Slave"). Antebellum era, the period before the Civil War occured, or before the year 1861, in the United States is used to relate to the enslavement of black American. In fact, the era was not merely about black, but also poor white. This study is purposed to describe the poor whites' life in antebellum America as reflected in Twelve Years As A Slave (1855), a narrative biography novel written by Solomon Northup. Set up the story in New York, Washingotn DC, and New Orleans, the author (and focalizer at once) told the story based on his own experience as a black who was captivated and sold into slavery for twelve years. Although the novel centered its story on black character, it also reflected the life of poor whites who were also being "enslaved" by their white counterparts. Through sociology of literature perspective, this study reveals that the character of poor white that represented through John M. Tibeats, Armsby, and James H. Burch came from Great Britain especially from Ireland. Mostly, they moved to America as incarcerated people. They lived under the poverty and some of them were the vagrants and petty criminals. Poor white during antebellum era in America was positioned in the lower social level. They were "enslaved" by their white master but more better compared to the black slaves. It can be noticed that poor white were positioned in low social level because of the socio-economic problem, while blacks were race and racism. Keywords: antebellum America, poor white, slavery, social class, American literature